What are the effects of interacting with, and reading to, a dog upon individual children’s classroom behaviour? - Emsley, Helen (2017)
The present research explored the impact of interacting with, and reading to, a dog on the classroom behaviour of seven primary school aged children. Relevant literature and theoretical underpinnings are discussed in line with the overarching themes of classroom behaviour and Animal-Assisted Interventions (AAI), focusing on the research which employs dogs as the chosen therapy animal. Reports from the past 27 years have shown low-level disruptive behaviour to be a cause for concern for teachers and parents (Elton, 1989; Steer, 2005; Ofsted, 2014). The literature also explores the possible theoretical unerpinnings of AAI, with a particular focus upon Attachment Theory (Bowlby, 1959). The literature considers how this theory may be applied to Human-Animal Interactions and what impact this may have for children bonding to animals in school. Currently, no research exists which explores the impact of AAI on behaviour once the child has returned to the classroom and the current study wished to address this. A single-case experimental design (SCED) was implemented with seven participants. Weekly data was collected through observational measures regarding classroom behaviour. This data was split into four categories: on-task behaviour (where the participant was actively or passively engaged in learning); off-task motor behaviour (the participant was out of their seat unnessarily, swinging on their chair or fiddling with equipment); off-task verbal behaviour (talking out of turn, calling out or making unnessary noises); off-task passive behaviour (staring out of the window, watching another peer). The results indicated positive effects in at least one area for six participants. The highest gains were demonstrated in off-task verbal behaviour, where improvements were observed in the behaviour of four participants. The present research provides tentative further evidence for the impact of interacting with and reading to a dog as an intervention for classroom behaviour. The discussion considered the nature of the design as a limitation, as SCEDs limit the generalisability of the findings. Furthermore, the limitations around observational measures are discussed, alongside the variables which may have affected the results, including the variability of the intervention itself between participants and differences between predisposiitons towards dogs. The conclusions recommend additional research into the use of canine-assisted interventions in schools and the Educational Psychologist’s place within this.